(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The current research aims to identify the research self-efficacy of postgraduate students, to achieve the objectives of this research, the researcher built a measure of research self-efficacy, which was in the final form of 37 paragraphs. The paragraphs were divided into 6 fields, was the self-efficacy related to the definition of the research, the theoretical framework, previous studies, research methodology and procedures, the presentation, interpretation and discussion of the results, conclusions, recommendations, suggestions and documentation. It have allocated the following alternatives that always apply to me, often apply to me, sometimes apply to me, rarely apply to me, never apply to me, give it weighs 1, 2, 3, 4 and 5 respectively. After confirming the validity of the tool through validity and reliability indicators, the researcher applied the research tool to a sample of 200 postgraduate students at the University of Wasit, after data collection and statistical processing, using the one-sample T-test, post-test for two independent samples, pearson Correlation Coefficient, Cronbach’s Alpha reliability coefficient, Z-test, Chi-square, multiple regression coefficient, a set of equations for descriptive measures, the arithmetic mean, the median, the mode, the standard deviation, the variance, the skewness, the kurtosis, the range. The researcher concluded that postgraduate students have a good degree of research self-efficacy.